2019
DOI: 10.3389/fpsyg.2019.01165
|View full text |Cite
|
Sign up to set email alerts
|

A Spanish Adaptation of the Computer and Mobile Device Proficiency Questionnaires (CPQ and MDPQ) for Older Adults

Abstract: Technology can help support the goal of many older adults to live independently, though cognitive, attitudinal, and other barriers often result in a “digital divide” in which older adults use and adopt new technology at a lower rate compared to younger adults. Due to the many potential benefits of technology it is not surprising that interest in tools that assess technology proficiency among older adults has increased. These tools can help support older adult technology research and training. However, to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 23 publications
3
43
2
3
Order By: Relevance
“…Younger people typically score higher on digital proficiency measures. Our study showed higher mobile proficiency compared to other studies of adults without hearing impairment (Moret-Tatay et al, 2019;Roque & Boot, 2018). However, computer literacy in this study is slightly lower than for adults with significant computer experience, where older adults were less computer proficient (Boot et al, 2015).…”
Section: Discussioncontrasting
confidence: 72%
“…Younger people typically score higher on digital proficiency measures. Our study showed higher mobile proficiency compared to other studies of adults without hearing impairment (Moret-Tatay et al, 2019;Roque & Boot, 2018). However, computer literacy in this study is slightly lower than for adults with significant computer experience, where older adults were less computer proficient (Boot et al, 2015).…”
Section: Discussioncontrasting
confidence: 72%
“…The lower preference for technology adoption has also been related to age (e.g., because of their lower proficiency). Moret-Tatay et al [ 53 ] found that older adults showed lower scores in mobile device and computer proficiency than younger adults. Consequently, adapted computer systems for older people have been designed to reduce the barriers that this population encounter.…”
Section: Discussionmentioning
confidence: 99%
“…These validated questionnaires have demonstrated significant relationships with the length and frequency of use of a specific technology [ 20 ]. Internal consistency for each scale is high with Cronbach’s α≥.98 [ 20 , 23 , 29 ].…”
Section: Methodsmentioning
confidence: 99%